Put Your Big Girl Knickers on! The Experiences of Two Female Leaders in New Zealand Primary Schools Turning Schools Around - Cook, Sheralyn (Frontiers in Education, 2020)
This chapter examines the experiences of two female leaders in New Zealand state primary schools and their experiences of turning their schools around. Leading schools through times of change and challenge is complex, especially when issues of school underperformance and student achievement are intertwined. In some instances, such circumstances result in educational authorities imposing an intervention such as a ‘turnaround’ program. Each year a small number of New Zealand schools are considered ‘underperforming’ and require external leadership assistance, usually from the Ministry of Education. This support is implemented through a statutory intervention mechanism aimed to address underpinning issues such as governance and leadership matters, low student academic achievement, issues of finance, and student and staff safety and wellbeing (Ministry of Education, 2017). While statutory interventions have been enacted in New Zealand since 1994 as a mechanism to ‘turn a school around’, there is little research about what this experience is like for educational leaders in primary (elementary) schools, or how it affects their professional and personal lives. Within the turnaround school literature, educational leaders are often positioned as ‘heroic leaders’, usually male, seeking to change the school’s climate and culture. However, there is little literature discussing how female educational leaders approach school recovery processes. With sparse acknowledgement of the effects this work has on a leader's professional and personal life, it is within these spaces that this research on female leaders’ experiences is situated. This study was part of a doctoral research project undertaken in 2016 to explore New Zealand primary school leaders’ perceptions and experiences of working to turnaround schools and addressing complex and challenging circumstances within their schools and communities. Using Dewey’s theory of experiences, the professional and personal experiences of two female leaders’ leading such schools are focused on to understand how their leadership is, in Clandinin and Rosick’s (2007) terms, constituted, shaped, expressed and enacted. The research revealed the professional and personal struggles both women encountered in their journey to turn their schools around, and contributes critical findings to the research focused on women’s experiences when turning schools around.